(untitled) (Bangladesh Journal of Animal Science, 2018)
This study was conducted to evaluate microbial load of beef meat during handling and selling in market. Total 12 samples were collected from K.R market, Sheshmore market, Kewatkhali bazaar and Mymensingh Sadar market. These samples were subjected to determine Total Viable Count (TVC), Total Coliform Count (TCC) and Total Yeast and Mould Count (TYMC) by using standard protocol at 0 hr, 2hrs and 5hrs time intarvel. The microbial counts of beef at different markets were high but there were no significant differences (p>0.05) among the markets. In every cases with the increased of time interval all types of microbial count increased significantly (p<o.o1) than the initial time. Microbial contamination of beef occurs as plant workers and machinery repeatedly touch contaminated surfaces and the carcass. Thoughtful design of operating procedures, especially for flaying and evisceration, can greatly reduce this problem. Frequent washing and sanitizing of hands, tools, and machinery is required in order to remove bacteria before they reach the exposed surface of the carcass. Bang. J. Anim. Sci. 2017. 46 (4): 244-248